Transmission line with gaseous cavitation - Chen, Junting. (2011)
A comprehensive study on the development of the gaseous cavitation model has been presented in this study.The purpose of this study is to develop an improved cavitation model to closely predict the pressure transients for gaseous cavitation conditions.From the prediction obtained from both the column separation method and two-phase homogenous cavitation model, errors can be identified in areas where severe cavitation is taking place. Hence an improved two-component two-phase cavitation model with the implementation of an additional gas term has been developed herein.Foremostly, the governing equations with the implementation of the gas term are developed. Following, the method of characteristics is employed to simplify the governing equations into four ordinary equations.Thus an enhanced cavitation model shall be developed to predict the inception and severity of cavitation taking place. In addition, the concept of theory and method use to solve the model has also been presented.